Elamite Problems. Albert Reckitt Archaeological Lecture - Mallowan, Max (1969)
British Academy 1969. Reprint From the Proceedings of the British Academy, Volume LV, 255-292, 13 fig., 8 pl.; ersch. 1970; 45p.